Investigation of the Lipid-Lowering Effect of Vitamin C Through GSK-3β/β-Catenin Signaling in Zebrafish - Liu, Dongwu; Yu, Hairui; Pang, Qiuxiang; Zhang, Xiuzhen (Frontiers in Physiology, 2018)
Vitamin C (VC) is an essential nutrient for most fish species due to the absence of L-gulonolactone oxidase in fish body. As an essential nutrient for fish species, VC plays a significant role in maintaining the physiological functions and improves the growth performance, immunity, and survival of fish. In this study, zebrafish were treated with 8.2, 509.6, and 1007.5 mg/kg VC diets for two weeks and the muscle samples were collected for gene expression and biochemical index analysis. The result indicated that 509.6 mg/kg and 1007.5 mg/kg VC diets inhibited GSK-3β expression and induced the expression of β-catenin in the muscle of zebrafish. The mRNA expression of CCAAT/enhancer binding protein a (C/EBPa) and fatty acid synthase (FAS), FAS activity, and the content of glycerol and triglyceride (TG) were decreased in the muscle by 509.6 mg/kg and 1007.5 mg/kg VC diets. In addition, GSK-3β RNA was interfered in zebrafish fed with 8.2 mg/kg and 1007.5 mg/kg VC diets. It was found that GSK-3β RNA interference induced the mRNA expression of β-catenin, but decreased the mRNA expression of C/EBPα and FAS, FAS activity, as well as the content of glycerol and TG in the muscle of zebrafish. In ZF4 cells, the mRNA expression of GSK-3β, C/EBPα, and FAS was decreased, but β-catenin expression was increased by 0.1 mmol/L and 0.5 mmol/L VC treatments in vitro. The glycerol and TG content as well as FAS activity in ZF4 cells were decreased by 0.1 mmol/L and 0.5 mmol/L VC treatments. Moreover, the result of western blot indicated that the protein expression level of GSK-3β was significantly decreased and that of β-catenin was significantly increased in ZF4 cells treated by 0.1 and 0.5 mmol/L VC. The results of in vivo and in vitro studies corroborated that VC exerted the lipid-lowering effect through GSK-3β/β-catenin signaling in zebrafish (Danio rerio).